2015
DOI: 10.1115/1.4028766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Volute Curvature on Performance of a Low Specific-Speed Centrifugal Pump at Design and Off-Design Conditions

Abstract: The effects of the volute geometry on the head, efficiency, and radial force of a low specific-speed centrifugal pump were investigated focusing on off-design conditions. This paper is divided into three parts. In the first part, the three-dimensional flow inside the pump with rectangular volute was simulated using three well-known turbulence models. Simulation results were compared with the available experimental data, and an acceptable agreement was obtained. In the second part, two volute design methods, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…They found that the pulsation in leakage through the impeller-tongue gap increased by 30% when the flow rate increased by 60% from the rated condition. Alemi et al [21] and Yang et al [22] reported the influence of cross-sectional shape on the hydraulic performance of a centrifugal pump and found that the circular cross sectional shape could provide a higher pump head and efficiency than trapezoidal and rectangle shapes. Bowerman et al [23], Chan et al [24], and Chang et al [25] reported that reducing the crosssectional area could offset the optimal efficiency point to a smaller flow rate condition and result in a steeper pressure fall at the pump outlet, specifically under large flow rate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the pulsation in leakage through the impeller-tongue gap increased by 30% when the flow rate increased by 60% from the rated condition. Alemi et al [21] and Yang et al [22] reported the influence of cross-sectional shape on the hydraulic performance of a centrifugal pump and found that the circular cross sectional shape could provide a higher pump head and efficiency than trapezoidal and rectangle shapes. Bowerman et al [23], Chan et al [24], and Chang et al [25] reported that reducing the crosssectional area could offset the optimal efficiency point to a smaller flow rate condition and result in a steeper pressure fall at the pump outlet, specifically under large flow rate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the fluid flow passing through the turbine is performed by using RANS equations. Among the turbulence models, the most suitable model to simulate turbomachines is the − model [34]. The − turbulence model is recommended by Menters [35][36][37] and has positive features of the − and − models simultaneously.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…"CU= x_iLt |xv=@R |xUOvy w x_iLt |OwQw |xUOvy 'u; w CU= |Oa@xU COWx@ x_iLt uwQO u=}QH xm Ov=xO=O u=Wv u}kkLt w [5w4] OvDU}v u=}QH Q=DiQ j}kO |v}@V}B x@ QO=k |Oa@wO w |Oa@l} |=ypOt xO=iDU= u}W}B |@ QHD G}=Dv |HvUQ=@Da= w O}rwDR=@ |= Q@ u=wD|t '=ypOt u}= R= u=}QH Q=DiQ j}kO |Q}oxR=Ov= Qw_vtx@ |Q}oxR=Ov= |=y|SwrwvmD |xaUwD "OQm |xUOvy u=wD|t = Q u; p}rO xm Ow@ Oy=wN Q@xv} Ry w OwOLt 'x_iLt uwQO R= xO=iDU= p=Lu}= =@ [6] "CUv=O u=}QH O=}R VNQJ COW w x_iLt |xO}J}B u=mt= 'u=}QH |Oa@xU |R=UpOt w 2 |D=@U=Lt Cq=}U l}t=v}O |=yl}vmD '=yQwUQBtm R= xO=iDU= =@ p=}U |R=UxOQWi |Qw=: vi 'hrDNt`}=vY |xaUwD =@ u=}QH |=yQwUQBtm '|Qw=: vi |xaUwD u}= QO "CU= xDW=O |vwRi=RwQ CiQW}B |QwLt |=yQwUQBtm Q@ 'OwOLt |=y=[i w sm |=y|@O QO =yu; OQ@Q=m xm |a=aW OQmrta Ow@y@ "OvQ=O |}xOQDUo OQ@Q=m w Ov=xOQm^iL = Q OwN x=o}=H 'OQ=O K}HQD |= RH= |xv}y@ |L=Q] OvtR=}v '|OQmrta |xOwOLt VQDUo Q=vm QO =yQwUQBtm u}= C=ar=]t uwvm=D "CU=y|oO}J}B uDiQoQ_v QO =@ u=}QH j}kO |UQQ@ T=U= Q@ =yu; =@ "CU= xDiQo CQwY u; QRw}i}O w QwUQBtm |xv=wQB |wQ |O=}R |@ QHD w |OOa OQwt QDsm 'u; uwQO u=}QH Q=DiQ |v}@V}B w 1 x_iLt |L=Q] |xar=]t p=L u}= u=}QH 'x_iLt |xO}J}B |xUOvy u=wD|t u; p}qO R= xm [1] 'CU= xDiQo Q= Qk xHwD 'x_iLt QO u=}QH Q=DiQ "OQtWQ@ = Q u; uwQO |=}=B=v w xDiW; COWx@ '|Oa@xU qt=m pwUt xOvU}wv "1394 12 [7] u= Q=mty w QO}; |wQ |y@=Wt Q=m R}v [8] [10] "OW |iQat x=Q= u; Ow@y@ |= Q@ |WwQ w CiQo Q= Qk Qrwt w wS xHwD OQwt x_iLt |xv=@R QF= OvO=O u=Wv w OvOQm |UQQ@ = Q |irDNt |UOvy |=yQDt= Q=B u= Q=mty w nv=}m [11] "OW |tr=a [3] [27] "CU= xOW |Q}oxR=Ov= QwUQBtm |HwQN w |OwQw QO 24 |H`wv |=ypBwmwtQD \UwD =tO xm |}=y=QHt \UwD l}D=DU= |=yQ=Wi w CwD}B xrwr \UwD pm |=yQ=Wi "OwW|t Q=Wi |=yM= QwU w CwD}B |=yxrwr "OvwW|t |Q}oxR=Ov= xOW O=H}= xrwr Q=OH QO |=yQD}tUv= QD R= xO=iDU= =@ Q=Wi w OvwW|t pYw Q=Wi |Q}oxR=Ov= sDU}U x@ l}D=DU= R= xO=iDU= u=mt= QwUQBtm |@O |Q}oxR=Ov= x=oDU}= QO "OwW|t |Q}oxR=Ov= 25 Q=Wi uwO=t |Qwv GvUQwO l} R= 'QwO VHvU |= Q@ w OQ=O OwHw T}i} Q= =} Twtr@ [16] "OwW|t x_Lqt 15 pmW QO uwtR; QDU@ |xQ=wKQ] "OwW|t xO=iDU= 26 RtQk |y=oW}=tR; G}=Dv =@ |OOa G}=Dv |xU}=kt j} Q] R= |OOapOt |HvUQ=@Da= 'xv=wQB pt=W = RH= Q=Wi Ci= Q}O=kt '|OQmrta |=yuwtR; R= GDvt Q}O=kt |= Q@ Qo}O |WywSB QO 'x_iLt |vwt=Q}B Q=Wi Q}O=kt |= Q@ u}vJty w x_iLt w QRw}i}O |OOa G}=Dv |HvUQ=@Da= 'VywSB u}= QO [28] "CU= xOW s=Hv= u=oOvU}wv u}ty R= uwtR; G}=Dv =@ u; |OQmrta G}=Dv …”
mentioning
confidence: 99%